Identification and functional characterization of natural human melanocortin 1 receptor mutant alleles in Pakistani population. (22nd September 2015) - Shahzad, Mohsin; Sires Campos, Julia; Tariq, Nabeela; Herraiz Serrano, Cecilia; Yousaf, Rizwan; Jiménez‐Cervantes, Celia; Yousaf, Sairah; Waryah, Yar M.; Dad, Haseeb A.; Blue, Elizabeth M.; Sobreira, Nara; López‐Giráldez, Francesc; et al.
Summary Melanocortin 1 receptor (MC1R), a Gs protein‐coupled receptor of the melanocyte's plasma membrane, is a major determinant of skin pigmentation and phototype. Upon activation by α‐melanocyte stimulating hormone, MC1R triggers the cAMP cascade to stimulate eumelanogenesis. We used whole‐exome sequencing to identify causative alleles in Pakistani families with skin and hair hypopigmentation. Six MC1R mutations segregated with the phenotype in seven families, including a p.Val174del in‐frame deletion and a p.Tyr298* nonsense mutation, that were analyzed for function in heterologous HEK293 cells. p.Tyr298* MC1R showed no agonist‐induced signaling to the cAMP or ERK pathways, nor detectable agonist binding. Conversely, signaling was comparable for p.Val174del and wild‐type in HEK cells overexpressing the proteins, but binding analysis suggested impaired cell surface expression. Flow cytometry and confocal imaging studies revealed reduced plasma membrane expression of p.Val174del and p.Tyr298*. Therefore, p.Tyr298* was a total loss‐of‐function (LOF) allele, while p.Val174del displayed a partial LOF attribute.